Pengembangan Buku Bacaan Berbasis Pendekatan Montessori Bermuatan Kearifan Lokal Bima untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas II SD Negeri Rada - Afrianti, Arini; Nanang Diana; Sulfahri; Nunung Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Montessori reading book containing Bima local wisdom that meets the criteria of validity, practicality, and effectiveness in improving the beginning reading skills of second-grade elementary school students. This study employed a Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The study subjects consisted of 17 second-grade students at Rada Public Elementary School. Data collection techniques included expert validation questionnaires, student response questionnaires, and beginning reading ability tests administered in the form of pre- and post-tests. The results showed that the developed product had a very high level of validity, with assessments from media experts at 90%, material experts at 92.5%, and lesson plan validators at 92.5%. Furthermore, the media's practicality was classified as very good, with a student response rate of 96.17%, indicating that the media was easy to use and engaging for students. In terms of effectiveness, this learning medium has been proven to improve students' early reading skills, as demonstrated by the increase in the number of students in the very advanced category from 6 to 13, and an average N-Gain score of 0.38, which falls within the moderate category. Thus, Montessori reading books containing Bima local wisdom are deemed suitable for use as innovative learning media that not only improve students' early reading skills but also strengthen local culture-based literacy in elementary schools.